Endoscopic submucosal dissection for superficial rectal tumors: prospective evaluation in France - Rahmi, Gabriel; Hotayt, Bilal; Chaussade, Stanislas; Lepilliez, Vincent; Giovannini, Marc; Coumaros, Dimitri; Charachon, Antoine; Cholet, Franck; Laquière, Arthur; Samaha, Elia; Prat, Frédéric; Ponchon, Thierry; Bories, Erwan; Robaszkiewicz, Michel; Boustière, Christian; Cellier, Christophe (Endoscopy, 2014)
Background and study aims: Endoscopic submucosal dissection (ESD) provides a high en bloc resection rate for superficial colorectal tumors. The aims of this study were to assess the feasibility of ESD in France and to evaluate the complete resection rate at 1 year.Patients and methods: Patients with superficial rectal tumors ≥ 10 mm in size were prospectively included in the study at nine French expert centers between February 2010 and June 2012. The study was stopped temporarily because of a high complication rate. Study recruitment resumed following remedial action. Results: A total of 45 patients were included (mean age 67 years; 24 males). The immediate perforation rate was 18 % (n = 8), and salvage surgery was not required. Six patients (13 %) had late bleeding, which was treated endoscopically in five patients and surgically in one patient who had required blood transfusion. The mortality rate was zero. The en bloc resection rate was 64 % (29/45), and the curative R0 resection rate was 53 % (24/45). Three patients (7 %) had an invasive tumor (two sm1, one T2). At 1-year follow-up, endoscopic examinations showed complete resection in 38 /43 patients (88 %). At the end of the study, after the remedial action, the en bloc resection rate had increased from 52 % to 82 %, and the perforation rate had decreased significantly from 34 % to 0 %.Conclusions: The study reflects the initial prospective experience of ESD in France, and suggests that curative R0 resection rates should increase and complication rates should decrease with experience and corrective actions.